Research on the Construction of Entrepreneurial Competency Quality Model for Entrepreneurs - Liu, Ni (International Journal of Global Economics and Management, 2024)
Entrepreneurial competence refers to the knowledge, skills, abilities and characteristics required by an outstanding entrepreneur to be competent for entrepreneurial tasks and achieve high entrepreneurial performance, which is manifested in the comprehensive ability to identify, pursue opportunities, acquire and integrate resources in the entrepreneurial process. As the core figure of entrepreneurship, entrepreneurs play a vital role in entrepreneurship. For the start-up enterprises before Round A, the resources are in short supply in all aspects and the company mechanism is not perfect, so the competence of entrepreneurs is particularly important, which greatly affects the direction and result of entrepreneurship. Therefore, it is of great significance to build a competency model for entrepreneurs to improve the success rate of entrepreneurship and promote the healthy development of entrepreneurial enterprises.